A new method for cost of renewable energy production in Algeria: Integrate all benefits drawn from fossil fuel savings. (April 2016) - Akbi, Amine; Yassaa, Noureddine; Boudjema, Rachid; Aliouat, Boualem
Abstract: The high generation cost of renewable energy is one of the main barriers to their development and large-scale deployment. This is the case of Algeria, in which despite its significant renewable energy potential, more than 96% of electricity is generated with gas turbines to cover increasing national demand. This choice is also driven by the important natural gas reservoirs in Algeria in addition to the low cost of electricity that is generated by this fossil fuel. The purpose of this paper is to investigate the cost of electricity production from a renewable source, substituting conventional fossil fuel processes. An economic value can be captured through the trade of greenhouse gas emissions and the reallocation of fuel savings to export. This approach is particularly well supported considering the growing local demand for natural gas, threatening the country's natural gas export capacity in which the economy of Algeria is tightly dependent. The conventional evaluation of the generation cost of electricity, using the Levelized Cost Of Electricity (LCOE) and the cost structure of electricity production is selected for comparing the cost of electricity generation from gas power and photovoltaic plants. The environmental benefits and their financial valuation mechanisms are discussed. To illustrate all these parameters, a case study of a photovoltaic plant with a capacity of one megawatt (1 MW) installed in Algeria is presented and the potential benefits in terms of fuel savings and CO2 eq emission assessed.